Music in African-American literature: the experience of the intermedial analysis in the novels of Z. N. Hurston - Afanasyeva, Yuliana A. (Journal of the Belarusian State University. Philology, 2023)
The article presents the specifics of intermedial connections in the novel work of Z. N. Hurston. The prerequisites that determined the vector of development of African-American culture during the Harlem Renaissance are highlighted. The inclusion of musical elements in the authentic literature of the first half of the 21st century is justified. Special attention is paid to the author’s manner of involving the musical narrative in the text, the interaction of extra- and intracompositional variants of intermediality in it. The theoretical and practical significance of the study consists in considering the analysis of specificity of intermediate approach used by Z. N. Hurston in the exploitation of musical structures in prose. Correlations of musical and verbal are shown taking into account the author’s style features and modernist trends of authentic culture, which allows us to study in more detail the specifics of Z. N. Hurston’s work and African-American prose of the Harlem Renaissance period in general.
Keywords: African-American literature; blues; jazz; Harlem Renaissance; vernacular; intermediality; signification